ANALISIS RESIKO PENDAPATAN USAHATANI BUAH NAGA MERAH DI KABUPATEN OGAN KOMERING ULU (JASEP, 2017)
This research carried out in the district OKU, collect data on the location of the research conducted in November until December 2016. The purpose of this study was to calculate the income of farmers in the farming red dragon fruit in the district OKU. The second objective to analyze the level of risk in the red dragon fruit farming OKU district. The method used is survey method. To analyze the risk of income DAK red dragon fruit farmers using agricultural bureau indicators DAK holticultura crops OKU District, 2015 to test the red dragon fruit farm income using a formula according to income Soekartawi, 1995 further to examine the risk of the red dragon fruit farm income using a formula according to Barry in Ihsannudin, 2011. The results of this study the average revenue generated by the red dragon fruit farmers in the amount of USD 157.169.267 per year and the risk of the dragon fruit farm income in the district OKU with coefficient of variation, which means CV 0,0001128057 < 0,5, then the value of L > 0, then the red dragon fruit farming will likely avoid making losses. Income owned by farmers will affect the behavior of farmers in the face.